Does Internalizing Disorders Predict a Decline in Friendship Quality? The Negative Impacts of Depression and Anxiety on Friendship Quality: [Apakah Permasalahan Internalisasi Memprediksi Penurunan Kualitas Persahabatan? Dampak Buruk Depresi dan Kecemasan terhadap Kualitas Persahabatan] - Wicaksono, Banyu; Izzaty, Rita Eka; Ayriza, Yulia; Hutagalung, Fonny Dameaty (Faculty of Psychology, Universitas Surabaya, 2022)
Friendship is one of the forms of interpersonal relationship which may be experienced by people at some point in their lives. Friendships play larger roles when people move into adolescence, when peers begin to play larger roles. However, studies concerning friendship tend greatly to be focused upon mental health benefits for adolescents and their role as factors protective against mental health problems, predominantly internalizing disorder. Nonetheless, several of the latest pieces of research indicate that friendship does not always provide protection against internalizing disorder. Experts in the field of developmental psychopathology have recommended looking at the connection between friendships and internalizing disorder from a different viewpoint. Not just viewing friendships as protection against internalizing disorder, there are guidelines asking about the effects of internalizing disorder influencing friendships. This study attempted to delve deeper into whether the internalizing disorder such as depression and anxiety, regarding two indexes of the features of friendship (the positive features of friendship and the negative features of friendship), with non-clinical adolescents in the South East Asian context, involving 400 Indonesian participants (84% female adolescents; 16% male adolescents; Mage = 16.04) and 269 Malaysian participants (73% female adolescents; 27% male adolescents; Mage = 15.86). The results of hierarchical linear regression analysis indicated that the increase in depression rates predicted lower levels of the positive features of friendships and higher levels of the negative features of friendship. Meanwhile, an increase in anxiety predicted higher levels of the negative features of friendship. Besides this, there were no significant results from regression analysis regarding anxiety and the positive features of friendship. Additional findings and practical implications are discussed comprehensively. Persahabatan merupakan salah satu bentuk relasi interpersonal yang akan dialami seseorang pada satu titik dalam kehidupannya. Persahabatan mengambil peran yang lebih besar ketika individu beranjak ke masa remaja, ketika teman sebaya mulai mengambil peran yang lebih besar. Hanya saja, studi tentang persahabatan cenderung banyak difokuskan pada manfaatnya bagi kesehatan mental remaja serta perannya sebagai faktor protektif terhadap masalah kesehatan mental, terutama masalah internalisasi. Namun, beberapa penelitian terkini menunjukkan bahwa persahabatan tidak selalu memberikan proteksi terhadap masalah internalisasi. Ahli-ahli psikopatologi perkembangan sebenarnya sudah memberi saran untuk melihat hubungan antara persahabatan dan permasalahan internalisasi dari sudut pandang yang berbeda. Alih-alih melihat persahabatan sebagai pelindung dari permasalahan internalisasi, ada arahan untuk bertanya apa efek masalah internalisasi mempengaruhi persahabatan. Studi ini mencoba untuk mendalami lebih jauh mengenai peran masalah internalisasi seperti depresi dan kecemasan kepada dua indeks fitur persahabatan (fitur persahabatan positif dan fitur persahabatan negatif) pada remaja non klinis dalam konteks Asia Tenggara, dengan melibatkan 400 partisipan Indonesia (84% remaja perempuan; 16% remaja laki-laki; Musia = 16,04) dan 269 peserta Malaysia (73% remaja perempuan; 27% remaja laki-laki; Musia = 15,86). Hasil analisis hierarchical linear regression menunjukkan bahwa naiknya depresi memprediksi fitur persahabatan positif yang lebih rendah dan memprediksi fitur persahabatan negatif yang lebih tinggi. Sedangkan naiknya kecemasan memprediksi fitur persahabatan negatif yang lebih tinggi. Selain itu, tidak ditemukan hasil yang signifikan pada hasil analisis regresi untuk kecemasan dan fitur persahabatan positif. Temuan tambahan dan implikasi praktis didiskusikan secara komprehensif.